Validation of three sympatric Thoracophelia species (Annelida: Opheliidae) from Dillon Beach, California using mitochondrial and nuclear DNA sequence data - Law, Chris J.; Dorgan, Kelly M.; Rouse, Greg W. (Zootaxa, 2013)
Thoracophelia (Annelida, Opheliidae) are burrowing deposit feeders generally found in the mid- to upper intertidal areas of sandy beaches. Thoracophelia mucronata (Treadwell, 1914) is found along the west coast of North America, including at Dillon Beach, CA. Two additional species, Thoracophelia dillonensis (Hartman, 1938) and T. williamsi (Hartman, 1938) were also described from this beach. These three sympatric species have been primarily distinguished by branchial morphology, and efforts to determine the validity of the species have been based on morphological, reproductive and ecological studies. Here we demonstrate using mitochondrial and nuclear DNA sequence data that these three species are valid. Mitochondrial Cytochrome c subunit 1 (COI) sequences show uncorrected interspecific distances of ~9–13%. We found no inter—specific differences in body color or in hemoglobin concentration, but found that reproductive males were pinkish-red in color and had lower hemoglobin concentrations than purplish—red reproductive females.